Four new species of free-living nematodes from shallow continental shelf of Portugal - Pinto, Taciana Kramer; Neres, Patricia Fernandes (Zootaxa, 2020)
Free-living marine nematodes of continental shelf of Portugal were studied through the goals of the Marine Biodiversity Information System Project (M@rbis 2015). Four species unknown to science and belonging to the families Axonolaimidae, Chromadoridae, Desmodoridae and Xyalidae are described. Besides Hypodontolaimus golikovy, Hypodontolaimus portuguese sp. n. is the only species in this genus which lacks precloacal supplements and gubernaculum but differs from the former mainly in cephalic setae length and amphidial fovea features. Metachromadora aliusa sp. n. doesn’t have a unique diagnostic character, differing in many aspects from the other species of the genus instead, mainly teeth number in the buccal cavity, size of the cephalic setae and the amphidial fovea, velum presence in the spicules, number and shape of the precloacal supplements. The main character of Odontophora sinapophysis sp. n. is the absence of apophysis in the gubernaculum. Stylotheristus multipapillatus sp. n. is characterized by the presence of precloacal supplements (papilliform) and the gubernaculum formed by only a piece.